Enhanced system usability scale using the software quality standard approach - Thamilarasan, Yarshini; Raja Ikram, Raja Rina; Osman, Mashanum; Salahuddin, Lizawati; Wan Bejuri, Wan Mohd Ya'akob; Kanchymalay, Kasturi (ETASR, 2023)
The objective of this paper is to improve the current System Usability Scale (SUS) and assess its applicability in the context of Learning Management Systems (LMS). The need to evaluate the usability of systems has become increasingly important in today's market, as it can have a significant impact on the user experience. In light of the COVID-19 pandemic, e-learning has become an essential tool for students, making LMS an appropriate research case study. Through a comprehensive literature review, it was discovered that SUS is the most widely used tool for evaluating system usability. However, SUS fails to satisfy some of the usability criteria outlined in ISO 9126 and ISO 9241-11. Therefore, this paper proposes an enhanced SUS model and its conceptual framework to address these limitations. The proposed model was validated using a case study approach, involving subject matter experts and software testing students, who evaluated the reliability of the enhanced SUS. Additionally, the existing and enhanced SUS models were evaluated based on an LMS case study and the results were used to calculate the enhanced SUS's reliability coefficient using Cronbach's alpha. The validation results show that the enhanced SUS has higher reliability with improved quality coverage compared to the original SUS. The proposed model has the potential to enhance the evaluation of system usability and, consequently, improve user experience.